Analisis Kinerja Kayawan Pada Pt Bina Usaha Warga Ciwandan-Cilegon - Suryaman Suryaman; Natalia Aprilianti (Universitas Serang Raya, 2020)
Abstrac This study aims to analyze the effect of employee selection, work placement of PT Bina Usaha Ciwandan, Cilegon. The method used is quantitative descriptive and associative one. The study was conducted from April to June 2019. The research population taken by saturated samples consisted of 54 persons. Data were collected using research instruments. Testing models and hypotheses using SPSS statistics version 24.0 windowsBased on the results of the study it can be concluded that : There is a positive and significant effect between the selection of employees, work placement and work motivation both partially and together with a contribution of 84.40% while the rest is related to other factors that are not taken into accountThe results of the research suggests that work performance at PT Bina Usaha Ciwandan-Cilegon can improve through the variable, namely work motivation related to the dimension of appreciation need through praise and acceptance given by the upliner for each employees’ works without underestimating them.